2006
DOI: 10.1152/ajpcell.00578.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cross bridges account for only 20% of total ATP consumption during submaximal isometric contraction in mouse fast-twitch skeletal muscle

Abstract: It is generally believed that cross bridges account for >50% of the total ATP consumed by skeletal muscle during contraction. We investigated the effect of N-benzyl-p-toluene sulfonamide (BTS), an inhibitor of myosin ATPase, on muscle force production and energy metabolism under near-physiological conditions (50-Hz stimulation frequency at 30 degrees C results in 35% of maximal force). Extensor digitorum longus muscles from mice were isolated and stimulated to perform continuous isometric tetanic contractions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
50
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 45 publications
7
50
4
Order By: Relevance
“…Furthermore, recent evidence (47) suggests that force production is not necessarily synonymous with glucose uptake but rather metabolic demand. In the present study, we used a more physiologically relevant contraction protocol than used previously (18,25,46), specifically by using lower stimulation frequencies, train durations, and contraction rates (54). Similar to the findings of Lefort et al (29), we found no difference in force production between muscles of AMPK-KD and WT mice (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, recent evidence (47) suggests that force production is not necessarily synonymous with glucose uptake but rather metabolic demand. In the present study, we used a more physiologically relevant contraction protocol than used previously (18,25,46), specifically by using lower stimulation frequencies, train durations, and contraction rates (54). Similar to the findings of Lefort et al (29), we found no difference in force production between muscles of AMPK-KD and WT mice (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Zhang et al (5) offer no mechanistic explanation for their result but suggest that it differs from previous data due to an effect of species or temperature or as a result of using submaximal activation. Points i and iii above argue against an effect of either species or temperature, and the dantrolene experiments (point iii) counter the idea that activation costs are higher at submaximal levels of activation.…”
contrasting
confidence: 70%
“…TO THE EDITOR: We are struck by the remarkable results contained in the article by Zhang et al (5). Put bluntly, if these results are independently verified, then a fundamental reappraisal of over four decades of muscle energetics will be required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the impairment in Ca 2ϩ uptake at fatigue has been well described, the importance of the ATP demand on SERCA regulation during repetitive contractions leading to fatigue is controversial (2, 28). Furthermore, little is known concerning whether the ATP cost of Ca 2ϩ handling during muscle activation is sufficient to regulate the SR Ca 2ϩ uptake kinetics and function during fatiguing contractile work.Several studies have assessed SR Ca 2ϩ uptake energy cost by blocking the activation of cross-bridge cycling using the compound N-benzyl-p-toluene sulfonamide (BTS) (5,7,22,30,40). This compound inhibits the affinity between myosin and actin (23) but does not affect Ca 2ϩ release and uptake in single muscle fibers (9,30,39).…”
mentioning
confidence: 99%